In defence of moral objectivity - McKaiser, Eusebius (Rhodes University, Faculty of Humanities, Department of Philosophy, 2003)
This thesis examines the problem of moral objectivity, which is constituted by the ontological, epistemological and motivational challenges. It gradually develops an account of moral objectivity that has the dual function of dealing with the enemies of moral objectivity as well as giving a positive account of what moral objectivity is. It establishes these aims by arguing for the following theses. The first set of arguments show that relativist theories of ethics provide us with no forceful grounds for being sceptical about moral objectivity. The second set of arguments deepens the response to those who are sceptical about moral objectivity. It does so by showing in greater detail how rationality plays a substantive role in our practical deliberation, our notion of agency as well as our reactive attitudes. These arguments provide further reasons why we should have faith in the possibility of developing an adequate account of moral objectivity. The last set of arguments provides the positive account of moral objectivity. This positive account ends with the discussion of a paradigmatic moral fact that gives full expression (to the features of moral objectivity that have been articulated and defended.
Keywords: Ethics; Objectivity